Modulation frequency and velocity variation of ions in a magnetized plasma sheath for different obliqueness of the field - Adhikari, Bhesha Raj; Lamichhane, Hari Prasad; Khanal, Raju (BIBECHANA, 2021)
The understanding of ion dynamics in magnetized plasma sheath is crucial for all applications of plasma. The velocity variation as well as modulation frequency of ions in a magnetized plasma sheath has been studied for different obliqueness of the magnetic field. The governing Lorentz force equation has been solved numerically for the given boundary conditions as applicable in the kinetic simulation of the sheath. For different obliqueness of the magnetic field, the average values, maximum amplitude, damping factor as well as frequency of oscillation are studied. The oscillating velocity components change at different rates depending on their orientation with respect to the field direction. Significant changes in the damping factor and modulation frequency has been observed for all components of velocity; however, the frequency of oscillation remains the same. As the obliqueness increases, shoulder natures in the components of velocity are observed. BIBECHANA 18 (1) (2021) 134-139